Hubert Lenoir et les révélations de l’affliction - Leguerrier, Louis-Thomas (Sens public, 2019)
Quand Hubert Lenoir, lors de son entrevue à Tout le monde en parle, a déclaré : « J’ai un peu le goût de me crisser en feu ces temps-ci », s’attirant les remontrances des animateurs qui jugeaient de mauvais goût le fait de dire une telle chose à la télévision, et de surcroît sur un plateau où se trouvait un invité ayant déjà fait une tentative de suicide, cela a provoqué un certain émoi dans le public, et on reprocha d’un côté au chanteur de banaliser le suicide et de l’autre aux animateurs d’avoir banalisé la détresse peut-être tout à fait sérieuse de celui-ci. Plutôt que de prendre part à ce débat, ou encore de proposer des stratégies pour briser les tabous au sujet du suicide, je voudrais aborder la dimension littéraire de ce fameux malaise télévisuel, qui est liée au malaise de l’époque contemporaine face à ce que j’appellerai ici la mise en scène de l’affliction.
Keywords: Hubert Lenoir; Susan Sontag; affliction; impudeur; indecency; literary; littéraire

“Saw You in the Dark”: Exploring Rufus Wainwright’s Emotional Vulnerability in Fan-Captured Live Performance Videos - Salerno, Stephanie (Performance Matters, 2019)

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

On feeling mighty real: devenir gay à Montréal pendant l’ère disco dans Funkytown, de Daniel Roby - Foerster, Maxime (Contemporary French Civilization, 2018)
Our catalogue of journals

La scène travestie qui est à l’origine du punk à Montréal - Desfossés, Félix B. (Vice, 2017)

Claude Vivier ou la machine désirante - Richard, Robert (Éditions Varia, 2017)
"Claude Vivier, compositeur méconnu au Québec, est né à Montréal en 1948. Il meurt assassiné à Paris en 1983. Il a fait ses études avec Gilles Tremblay et Karlheinz Stockhausen. Son œuvre – qui contient une quarantaine de titres – est inclassable, s'inspirant de ou bougeant à travers des époques très différentes de l'histoire de la musique, depuis le Moyen Âge jusqu'à la musique dite « spectrale » des années 1980. C'est une œuvre d'une grande originalité, qui a choisi la fuite hors des attentes ou des formes prévues et qui a cherché à délirer les continents, les langues, les peuples."–From publisher's website

Nightclubbing: Montréal’s Lime Light - Pemberton, Rollie (Red Bull Music Academy, 2016)
The Lime Light and its innovative DJ Robert Ouimet made Montreal a disco city during the ’70s. This is the club's story.

Montréal Rave: An Oral History - Borzeix, Olivier (Red Bull Music Academy, 2016)
Tiga, Christian Pronovost, Jeff Waye and more remember the golden era of raves in Montréal.

Robert Ouimet and Pierre Gagnon - Burns, Todd L. (Redd Bull Music Academy, 2016)
Explore the Red Bull Music Academy archive, tracing the global music institution’s more than 20-year history

De l’homosexualité à l’opéra - Champagne, Éric (L’Opéra : revue québécoise d’art lyrique, 2016)
Créée à l’Opéra de Montréal, l’œuvre de Kevin March, Les Feluettes, sur un livret de Michel Marc Bouchard, aborde de front une histoire d’amour entre deux hommes. Si les sujets homosexuels nous semblent communs dans la littérature, le théâtre et le cinéma, il faut se rendre à l’évidence qu’ils sont, du moins jusqu’à tout récemment, peu présents dans le monde de la musique, tous styles confondus. On entend beaucoup dire ces jours-ci que le genre de l’opéra, au public réputé conservateur, ne s’intéresse à cette thématique que depuis peu. Il s’agit en fait d’une demi-vérité, car s’il est vrai que l’homosexualité comme sujet principal n’est présent explicitement que dans des créations récentes, il se retrouve occasionnellement, caché ou crypté, dans diverses œuvres qui traversent son histoire vieille de plus de 400 ans.

Claude Vivier at the End - Goldman, Jonathan (Contemporary Music and Spirituality, 2016)

DJ Mini and Montreal’s Vulgar Dance Music - Madden, David (Dancecult, 2016)
This article advances claims about Montreal’s electronic dance music scene through mapping the career of one of the key actors who shaped the electroclash scene from the early 2000s onwards—music producer/DJ Mini (née Evelyne Drouin). By way of detailing the career of DJ Mini, this text attempts to add to the queer musical narratives currently emerging from music scene analyses. Counter to the experiences of many women DJs and musicians participating in heterosexual and male-dominated music scenes, Drouin received extensive mentoring and support from various informal queer social networks spread throughout the circuits of the city. Not only did she gain access to a local production network of equipment and skill sharing, Drouin was also given access to spaces where she was able to develop production skills on her own time and at her own pace. DJ Mini’s story offers a telling case for the ways in which the politics of access—institutional, social, technological—remain central to the vitality and inclusivity of local music scenes.

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Changing openness and tolerance towards LGBTQ singer-songwriters - Williams, Katherine (The Cambridge Companion to the Singer-Songwriter, 2016)
Most often associated with modern artists such as Bob Dylan, Elton John, Don McLean, Neil Diamond, and Carole King, the singer-songwriter tradition in fact has a long and complex history dating back to the medieval troubadour and earlier. This Companion explains the historical contexts, musical analyses, and theoretical frameworks of the singer-songwriter tradition. Divided into five parts, the book explores the tradition in the context of issues including authenticity, gender, queer studies, musical analysis, and performance. The contributors reveal how the tradition has been expressed around the world and throughout its history to the present day. Essential reading for enthusiasts, practitioners, students, and scholars, this book features case studies of a wide range of both well and lesser-known singer-songwriters, from Thomas d'Urfey through to Carole King and Kanye West.

Rufus Wainwright - Williams, Katherine (Equinox Publishing, 2016)
Canadian-American singer-songwriter Rufus Wainwright is famous around the world for his multi-faceted musical style, shown through both his recorded output and his engaging live performances. Katherine Williams combines aspects of his life story with scholarly readings drawn from several methodologies.

Rufus Wainwright sings "Grey Gardens": on Thomas Mann's "Death in Venice", Tadzio and his pop cultural "life" - Bałżewska, Katarzyna (Beyond Philology: An International Journal of Linguistics, Literary Studies and English Language Teaching, 2015)

L'esthétique rock queer : de C.R.A.Z.Y. à Xavier Dolan - Laverdière, Gabriel (Nouvelles vues. Revue sur les pratiques et les théories du cinéma au Québec, 2015)
L'analyse proposée des films C.R.A.Z.Y. (Jean-Marc Vallée, 2005), J'ai tué ma mère (Xavier Dolan, 2009), Les amours imaginaires (Dolan, 2010) et Laurence Anyways (Dolan, 2012) convoque trois perspectives : le rock, le camp et le queer. Dans ces films québécois, la musique rock semble orienter la narration et l'esthétique. Elle fait également le pont entre l'anticonformisme auquel renvoie le paradigme rock et l'identité marginale des personnages. L'esthétique de l'image se plie parfois à la bande sonore, qui encourage certains effets visuels. Cela dit, les films de Vallée et de Dolan se servent différemment de l'esthétique rock et du camp, ce qui s'accorde aux représentations distinctes qu'ils produisent eu égard à l'orientation ou à la diversité sexuelles et au genre. L'excès des films de Dolan, leur hyperréférentialité, leur jeu constant entre recherche d'émotions esthétiques et d'émois narratifs, leur fréquente suspension de la réalité contribuent à une écriture du différé dans laquelle les personnages queer jouissent d'une amplitude considérable, alors que dans C.R.A.Z.Y. la performance hyperbolique s'articule plutôt à une analytique de l'homophobie (sociétale et intériorisée) que le film s'efforce de dresser, sans pouvoir échapper à un certain malaise.

Vivier reenacted: Singing beyond masculine - Novak, Jelena (New Sound: International Magazine for Music, 2015)
Vivier: A Night Report is a kind of poetical archive of musical details, protocols, experiences, concepts, memories, fears, desires and sorrows connected to Canadian composer Claude Vivier's (1948-1983) unusual destiny. All characters from Marko Nikodijević's opera originate from Vivier's life and works but they are re-indexed, or reenacted differently. The countertenor voice of Vivier is what primarily makes him different from all the rest of the characters. Even it could be claimed that the rest of the voices are dominated by Vivier's vocal presence on stage. Vivier stands as symbol for minority, queer, vulnerable. During his short life he was trying to get his own voice, voice as the personification of freedom and possibility to be heard. Finally he gets vivid, imaginative opera in which both his physical and personified voices are shining by creativity that his art emanate. He gets his singing voice, and he finally gets heard.

Queering Discourses of Urban Decline: Representing Montréal's Post-World War II "Lower Main" - Podmore, Julie (Historical Geography, 2015)
In this paper, I examine how urban redevelopment and the regulation of public spaces in Montréal in the 1960s transformed the representations of the Lower Main, the city’s historic red-light and entertainment district. I argue that although the Lower Main had long been central to anti-urban discourses regarding heterosexual prostitution, by the 1960s the increased regulation of the city’s queer and trans populations changed its meaning as a representation of the inner city in decline. A central objective is to use this case study to queer discourses of urban decline by considering how heteronormativity was involved in the construction of the city’s sexual margins in the post-World War II period. A related objective is to call into question the narrative of “decline” itself by providing one example of the opportunities it created for queer place-making.

Shock, glam, punk - Desfossés, Félix B. (No Speed Limit (1964-1989). L’évolution du métal québécois, 2014)

Michel Louvain. Sans âge - Gignac, Benoît (Éditions Caractère, 2014)
Découvert au milieu des années 50, admiré et adulé, Michel Louvain fait encore battre les coeurs près de 60 ans après avoir amorcé sa carrière. Ce livre-coffret retrace le parcours irréprochable de cet artiste accompli, qui a remporté les honneurs autant pour ses performances sur disque, sur scène et à la télévision que pour son soutien à des causes sociales.

Claude Vivier: A Composer’s Life - Gilmore, Bob (University of Rochester Press, 2014)
Claude Vivier's haunting and expressive music has captivated audiences around the world. But the French-Canadian composer is remembered also because of the dramatic circumstances of his death: he was found murdered in his Paris apartment at the age of thirty-four. Given unrestricted access to Vivier's archives and interviews with Vivier's family, teachers, friends, and colleagues, musicologist and biographer Bob Gilmore tells here the full story of Vivier's fascinating life, from his abandonment as a child in a Montreal orphanage to his posthumous acclaim as one of the leading composers of his generation. Expelled from a religious school at seventeen for "lack of maturity," Vivier gave up his ambition to join the priesthood to study composition. Between 1978 and 1981 Vivier wrote the works on which his reputation rests, including 'Lonely Child', 'Bouchara', and the operas 'Kopernikus' and 'Marco Polo'. He went to Paris in 1982 to work on a new opera, the composition of which was interrupted by his murder. On his desk was the manuscript of his last work, uncannily entitled "Do You Believe in the Immortality of the Soul?" Vivier's is a tragic but life-affirming story, intimately connected to his passionate music. Bob Gilmore is a musicologist and performer and teaches at Brunel University in London. He is the author of 'Harry Partch: A Biography'.

Le Lunatique, « Le temps du changement » : Intimidation, ostracisme et homophobie dans le milieu hip-hop au Québec - Lamort, Kapois (Les boss du Québec. R.A.P. du fleur de lysée. Analyse socio-historique et sociologique du hip-hop dans la société québécoise, 2014)
Le tout premier livre monographique et scientifique axé sur la culture Hip-Hop au Québec, rédigé par Kapois Lamort, historien spécialiste diplômé de l’Université du Québec à Montréal ( UQAM); cet ouvrage retrace les 35 ans d’existence du H.I.P.H.O.P. à travers la société québécoise de 1979 à 2015

La construction sociodiscursive de l'image médiatique de la drag-queen Mado Lamotte. Les frontières de la transgression sociale - Laberge, François (Université Laval, 2013)
Selon la perspective interactionniste de la communication développée par Goffman (1973a, 1973b), l’image qu’un individu a de lui-même et qu’il tente de projeter sur les autres se construit au cours de l’interaction en fonction de représentations socialement partagées. Adoptant cette approche théorique, ma recherche vise à identifier, dans les interventions médiatiques de la drag-queen Mado Lamotte, les procédés discursifs qui participent à la construction de son image publique. L’analyse portera sur les actes de parole potentiellement menaçants (Brown et Levinson, 1987) et à leur amplification (Kerbrat-Orecchioni, 1990). Le corpus est constitué de 29 apparitions télévisées principalement extraites d’émissions de divertissement. La méthode d’analyse du discours (Charaudeau et Maingueneau, 2002) a permis de dégager les différents actes de parole menaçants (Venderveken, 1988) ainsi que les types de procédés par amplification (Vincent, Laforest et Turbide, 2008). L’analyse révèle trois dimensions de transgression sociale dans le modèle de construction de l’image de la drag queen : les normes interactionnelles, la frontière entre les domaines public et privé et l’identité de genre.
Accepted: 2018-04-19T21:50:05Z

Notre Clémence. D'amour et d'humour - Pedneault, Hélène (Éditions de l'Homme, 2013)
Humoriste, poète, monologuiste, comédienne: Clémence DesRochers s'est constamment réinventée au cours de sa prolifique carrière. Prenant la parole au nom des gens d'ici, elle a tour à tour exprimé avec justesse les joies et les peines des ouvriers, des femmes, des laissés-pour-compte et des homosexuels. Chaque fois, ses mots nous ont touchés droit au cœur, nous faisant à la fois sourire et réfléchir. Ce livre rend hommage au parcours exceptionnel d'une auteure profondément humaine, accessible et chaleureuse qu'un prénom suffit à désigner. Redécouvrez Clémence, la femme, l'artiste, la peintre du quotidien qui n'a jamais cessé d'esquisser notre portrait.

"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Number: 3 Publisher: Association Transpositon. Musique et Sciences Sociales
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype

De l’ombre à la lumière : fragments pour une analyse des trois premiers albums d’Ariane Moffatt - Doyon, Noémie (Canadian Folk Music, 2012)

Femme-acrobate, femme-automate : Le Fil de Camille et Le Cœur dans la tête d'Ariane Moffatt - Doyon, Noémie (Chanson et performance. Mise en scène du corps dans la chanson française et francophone, 2012)
La moustache de Brassens, la robe noire d'Edith Piaf, les paillettes de Claude François, les cheveux de Dalida ... Les chanteurs ont un corps indissociable de leurs chansons. Ce livre s'intéresse à la présence physique de la musique populaire, à sa performance sur scène et sur le disque. Voici observées les tensions sociales, sexuelles et identitaires qui sous-tendent la performance musicale

Le pouvoir créateur d’Alfred et de Clémence - Roy, Julie; Fortier, Hélène (Revue de Bibliothèque et Archives nationales du Québec, 2012)

Entre stabilité et mouvement : l'oscillation spatiale dans le diptyque "Want" de Rufus Wainwright - Mathieu-Lessard, Jeanne (Université Laval, 2011)
Ce mémoire propose l’analyse de chansons extraites du diptyque Want (formé des albums Want One et Want Two), de l’auteur-compositeur-interprète Rufus Wainwright, en regard des relations entre l’énonciateur et l’espace. La notion d’oscillation spatiale, définie en introduction, est au cœur de la situation de l’énonciateur et se déploie sous de multiples formes dans les cinq chansons à l’étude. « Oh What a World » et « I Don’t Know What It Is » sur Want One, « Hometown Waltz », « Memphis Skyline » et « Old Whore’s Diet » sur Want Two, ont été choisies pour la façon dont la relation à l’espace y agit de même que pour leur emplacement dans l’ensemble. La position de l’énonciateur mise en évidence dans chaque analyse s’inscrit au sein d’un parcours, que l’étude préliminaire du paratexte des albums aura d’ailleurs mis en évidence.

Performing ‘Judy’: The Creation and Function of Cover Personae in Popular Music in Rufus Wainwright's Judy Garland Concerts - O'Connell, Sam (Contemporary Theatre Review, 2011)

One Day in the Life of Rufus Wainwright - Hailand, Tim (Hailand Books, 2010)
One Day in the Life of Rufus Wainwright follows the singer-songwriter from New York City to Boston for his performance at the Boston Opera House, which featured his sister Martha Wainwright as a special guest. With an intro by NYC nightlife legend Cherry Vanilla and text from Rufus himself.

There Will Be Rainbows: A Biography of Rufus Wainwright - Lake, Kirk (Itbooks, 2010)
"No contemporary pop performer's work mixes innovation and tradition like Rufus Wainwright's. He is the son of singer, songwriter, actor Loudon Wainwright III and legendary Canadian folk singer Kate McGarrigle whose story is one of towering highs and rock bottom lows in which family influences, sexual experimentation, and a crystal meth addiction in the early 2000s have greatly contributed."

The Montreal Sailors' Institute and the Homosexual Sailor: A Model for Moral Reform in the Nineteenth and Twentieth Centuries - Renwick, Claire (Montreal as Palimpsest, 2010)

“Oh What a World”: Queer Masculinities, the Musical Construction of a Reparative Cultural Historiography, and the Music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
Keywords: Communication and the arts; Gay history; Gay rights; Historiography; Masculinities; Popular culture; Queer; Reparative reading; Rufus; Social sciences; Wainwright